Construct validity and test-retest reliability of the International Fitness Scale (IFIS) in Colombian children and adolescents aged 9-17.9 years : The FUPRECOL study (2017)
Background. There is a lack of instruments and studies written in Spanish evaluating physical fitness, impeding the determination of the current status of this important health indicator in the Latin population, especially in Colombia. The aim of the study was two-fold: to examine the validity of the International Fitness Scale (IFIS) with a population-based sample of schoolchildren from Bogota, Colombia and to examine the reliability of the IFIS with children and adolescents from Engativa, Colombia. Methods. The sample comprised 1,873 Colombian youths (54.5% girls) aged 9- 17.9 years. We measured their adiposity markers (waist-to-height ratio, skinfold thickness, percentage of body fat and body mass index), blood pressure, lipids profile, fasting glucose, and physical fitness level (self-reported and measured). A validated cardiometabolic risk index score was also used. An age- and sex-matched subsample of 229 schoolchildren who were not originally included in the sample completed the IFIS twice for reliability purposes. Results. Our data suggest that both measured and self-reported overall physical fitness levels were inversely associated with percentage of body fat indicators and the cardiometabolic risk index score. Overall, schoolchildren who self-reported "good" or "very good" fitness had better measured fitness levels than those who reported "very poor/poor" fitness (all p<0:001). The test-retest reliability of the IFIS items was also good, with an average weighted kappa of 0.811. Discussion. Our findings suggest that self-reported fitness, as assessed by the IFIS, is a valid, reliable, and health-related measure. Furthermore, it can be a good alternative for future use in large studies with Latin schoolchildren from Colombia. © 2017 Rodgers et al.